STUDENTS' DIFFICULTIES IN ENGLISH SPEAKING SKILL - Dayansyah, Oki; Kurniasari, Renny; Husna, Husnaini (Journal of English Education and Linguistics, 2024)
This study was conducted to find out students' difficulties in learning English speaking at SMAN 1 Tulung Selapan, OKI. The participants of this study were 6 students of XI IPA 1 using a purposive sampling method. The data were collected by using interview with 20 questions. The findings of this research revealed that there were students' difficulties in learning English speaking, as follows: (1) pronunciation was the biggest difficulty for students to learn to speak English. Some students said that it was very difficult to pronounce vocabulary that had different pronunciations because their mother tongue did not have the same pronunciation of the alphabet as Indonesian. Students have to learn a lot of how to pronounce English so that they would get used to it later. (2) Vocabulary was a challenge in itself, students often look for the right words to pronounce. Students find it quite difficult for themselves to determine the right words to use correctly in English conversation. In this case, students also have to memorize a lot of vocabulary to find the right words when speaking English. (3) some students were not confident, and shyness was the main problem in this study because they were afraid of being laughed at by their friends when make mistakes. The conclusion of this research indicated that those students of SMAN 1 Tulung Selapan had several difficulties in speaking English including lack of pronunciation, lack of vocabulary, and lack of self-confidence when speaking English because they were ashamed and afraid of being laughed at by their classmates. Keywords: Students’ difficulties, Learning, English speaking.